In Vivo Evaluation of Wound Healing Properties of Platanus orientalis L. - Somayeh Niknam; Arezoo Rastegari; Mahboubeh Bozorgi; Yasaman Vahedi-Mazdabadi; Mina Saeedi; Tahmineh Akbarzadeh (Tabriz University of Medical Sciences, 2022)
Background: According to the Iranian Traditional Medicine (ITM) references, Platanus orientalis L. possesses wound healing properties. Herein, we developed different topical formulations based on the ethanolic extract of P. orientalis leaves and evaluated its wound healing effects through an in vivo model. Methods: Hydroalcoholic extract of the leaves was obtained from ethanol 80% and it was evaluated for DPPH radical scavenging activity, total phenolic and flavonoid contents as well as the presence of tannins. Different topical formulations including ointment (D-O) and polymer film (D-F), were prepared and an in vivo test was run for 14 days in an excision wound model consisting of 5 groups of 6 rats. Results: The results indicated the higher efficacy of D-O compared with D-F, as wound surface area remarkably reduced within 14 days post-injury. Also, histological features including epitheliogenesis score, neovascularization, and collagen density indicated the potential wound healing effect of D-O. Conclusion: Wound healing properties of the ethanolic extract of P. orientalis leaves depended on the type of formulation and D-O was found to be much more potent than D-F, from reducing wound surface area, maximum epitheliogenesis score, proper neovascularization pattern, and early type I collagenization points of view.